2000
DOI: 10.1017/s1481803500007284
|View full text |Cite
|
Sign up to set email alerts
|

Pilot intervention to improve the documentation of pediatric injuries in the emergency department

Abstract: Objectives: Our goal was to determine the effectiveness of an intervention aimed at improving the emergency department (ED) documentation of pediatric injuries. Methods: All physicians and nursing staff in the ED of an urban teaching hospital and trauma centre underwent focused injury surveillance training and were instructed how to document 14 injuryspecific data elements. Pocket reminder cards were provided, and pediatric injury charts were flagged. Subsequently, random samples of pediatric injury charts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…printed education materials) in effecting lasting changes in physicians’ documentation behavior [15, 5861]. While the findings from our review tend to confirm that active interventions such as audit/feedback, reminders, or templates and/or multiple interventions may improve physician documentation, we did observe mixed results with respect to documentation comprehensiveness and accuracy when these interventions were introduced into ED settings [26, 44, 47, 48, 50, 51, 54, 55]. The quality of the studies identified in this review, and variability in settings, outcome measures, and intervention duration across studies may have contributed to this finding; when appropriately designed for the context or environment in which they will operate, these interventions may prove even more effective in supporting improvements in physician documentation.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…printed education materials) in effecting lasting changes in physicians’ documentation behavior [15, 5861]. While the findings from our review tend to confirm that active interventions such as audit/feedback, reminders, or templates and/or multiple interventions may improve physician documentation, we did observe mixed results with respect to documentation comprehensiveness and accuracy when these interventions were introduced into ED settings [26, 44, 47, 48, 50, 51, 54, 55]. The quality of the studies identified in this review, and variability in settings, outcome measures, and intervention duration across studies may have contributed to this finding; when appropriately designed for the context or environment in which they will operate, these interventions may prove even more effective in supporting improvements in physician documentation.…”
Section: Discussionmentioning
confidence: 69%
“…Four studies (one pre-post without control, one pre-post control, two prospective follow up with comparison) assessed the impact of multi-interventions on the quality of physician documentation [5255]. While all studies included an education component, they varied in the type and number of other interventions that were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Without specific prompting using standardized template charts, it seems unreasonable to expect front line staff to report a set of mandatory injury specific variables. Previous research from this region showed a modest increase in charting pediatric injury information with education 16 ; however, this increase may have been short lived. Finally, the use of known preventive injury strategies is also not collected routinely or in a standardized fashion.…”
Section: Discussionmentioning
confidence: 84%